Impact of One-Year Methadone Maintenance Treatment in Heroin Users in Jiangsu Province, China - Guohong Chen; Takeo Fujiwara (SAGE Publishing, 2009)
Context: Although the effectiveness of methadone maintenance treatment (MMT) is well-established in many countries, it is a relatively new therapy for heroin users in China. Jiangsu Province, a relatively wealthy province, set up 4 MMT clinics in February 2006. No previous studies have evaluated the impact of MMT in a wealthy Chinese province. Objective: The aim of this study is to evaluate the impact of a 1-year MMT among heroin users in Jiangsu Province. We investigated the impact of the treatment by examining the following outcomes: 1) reduction of heroin use, 2) increase of appropriate sexual intercourse, 3) reduction of antisocial behavior, 4) increase of better social and family relationships, and 5) HIV prevalence among heroin users in MMT clinics. Design and Setting: Repeated cross-sectional surveys were conducted before and after heroin users in Jiangsu Province received at least 1-year of treatment in the MMT clinics. A questionnaire survey was implemented for those who agreed to participate from March to April 2006, before the initiation of MMT (N = 554). The second survey was from August to September 2007 and was administered to those who received MMT for more than 1 year (N = 804). One hundred and ninety-six patients who were investigated in both surveys were included in a longitudinal study to evaluate the factors attributable to behavior change. Results: MMT helped in reducing the percentage of heroin injection and also improved social and familial relationships. Antisocial behavior, including theft, prostitution, and dealing in heroin, decreased after 1-year treatment in the MMT clinics. However, the percentage of patients using condoms was not statistically significant. No case was found to be HIV-positive among those who received more than 1 year MMT. In the longitudinal study of 196 patients who participated in both surveys, no specific demographic variables were found to be associated with heroin use, anti-social behaviors after 1-year MMT. Conclusions: MMT was thought to reduce heroin use, antisocial behaviors and HIV prevalence, and increased appropriate sexual intercourse behaviors and better social and family relationships among heroin users in a wealthy province in China, which was true regardless of gender, age, marital status, or working status.